Treg Cell Therapeutic Strategies for Breast Cancer: Holistic to Local Aspects - Hanwen Zhang; Oliver Felthaus; Andreas Eigenberger; Silvan Klein; Lukas Prantl (Cells)
Regulatory T cells (Tregs) play a key role in maintaining immune homeostasis and preventing autoimmunity through their immunosuppressive function. There have been numerous reports confirming that high levels of Tregs in the tumor microenvironment (TME) are associated with a poor prognosis, highlighting their role in promoting an immunosuppressive environment. In breast cancer (BC), Tregs interact with cancer cells, ultimately leading to the suppression of immune surveillance and promoting tumor progression. This review discusses the dual role of Tregs in breast cancer, and explores the controversies and therapeutic potential associated with targeting these cells. Researchers are investigating various strategies to deplete or inhibit Tregs, such as immune checkpoint inhibitors, cytokine antagonists, and metabolic inhibition. However, the heterogeneity of Tregs and the variable precision of treatments pose significant challenges. Understanding the functional diversity of Tregs and the latest advances in targeted therapies is critical for the development of effective therapies. This review highlights the latest approaches to Tregs for BC treatment that both attenuate Treg-mediated immunosuppression in tumors and maintain immune tolerance, and advocates precise combination therapy strategies to optimize breast cancer outcomes.